Incidence of RNA viruses infecting taro and tannia in East Africa and molecular characterisation of dasheen mosaic virus isolates - Dawit B, Kidanemariam; Amit C, Sukal; Adane D, Abraham; Joyce N, Njuguna; Francesca, Stomeo; James L, Dale; Anthony P, James, Robert M. Harding; Anthony P, James; Robert M, Harding (John Wiley & Sons, Ltd, 2021)
Abstract Taro (Colocasia esculenta) and tannia (Xanthosoma sp.) plants growing in 25 districts across Ethiopia, Kenya, Tanzania and Uganda were surveyed for four RNA viruses. Leaf samples from 392 plants were tested for cucumber mosaic virus (CMV), dasheen mosaic virus (DsMV), taro vein chlorosis virus (TaVCV) and Colocasia bobone disease-associated virus (CBDaV) by RT-PCR. No samples tested positive for TaVCV or CBDaV, while CMV was only detected in three tannia samples with mosaic symptoms from Uganda. DsMV was detected in 40 samples, including 36 out of 171 from Ethiopia, one out of 94 from Uganda and three out of 41 from Tanzania, while none of the 86 samples from Kenya tested positive for any of the four viruses. The complete genomes of nine DsMV isolates from East Africa were cloned and sequenced. Phylogenetic analyses based on the amino acid sequence of the DsMV CP-coding region revealed two distinct clades. Isolates from Ethiopia were distributed in both clades, while samples from Uganda and Tanzania belong to different clades. Seven possible recombination events were identified from the analysis carried out on the available 15 full-length DsMV isolates. Nucleotide substitution ratio analysis revealed that all the DsMV genes are under strong negative selection pressure.
Keywords: aroids, cucumber mosaic virus, Ethiopia, Kenya, plant viruses, potyvirus, rhabdovirus, Tanzania, Uganda